Finance-Led Growth in the OECD since the Nineteenth Century: How Does Financial Development Transmit to Growth? - Madsen, Jakob B.; Ang, James B. (The Review of Economics and Statistics, 2016)
It is well established in the literature that financial development (FD) is conducive to growth, and yet the channels through which FD affects growth are not well understood. Using a unique new panel data set for 21 OECD countries over the past 140 years, this paper examines the extent to which FD transmits to growth through ideas production, savings, fixed investment, and schooling. Unionization and agricultural share are used as instruments for FD. The empirical results show that FD influences growth through all four channels. In particular, ideas production is found to be the most important channel through which FD affects growth.